Plasma long noncoding RNA expression profile identified by microarray in patients with Crohn’s disease - Chen, Dong; Liu, Jiang; Zhao, Hui-Ying; Chen, Yi-Peng; Xiang, Zun; Jin, Xi (World journal of gastroenterology : WJG, 2016)
AIM: To investigate the expression pattern of plasma long noncoding RNAs（lnc RNAs） in Chrohn’s disease（CD） patients.METHODS: Microarray screening and q RT-PCR verification of lnc RNAs and m RNAs were performed in CD and control subjects, followed by hierarchy c l u s t e r i n g, G O a n d K E G G p a t h w a y a n a l y s e s. Significantly dysregulated lnc RNAs were categorized into subgroups of antisense lnc RNAs, enhancer lnc RNAs and linc RNAs. To predict the regulatory effect of lnc RNAs on m RNAs, a CNC network analysis was performed and cross linked with significantly changed lnc RNAs. The overlapping lnc RNAs were randomly selected and verified by q RT-PCR in a larger cohort. RESULTS: Initially, there were 1211 up-regulated and 777 down-regulated lnc RNAs as well as 1020 up-regulated and 953 down-regulated m RNAs after microarray analysis; a heat map based on these results showed good categorization into the CD and control groups. GUSBP2 and AF113016 had the highest fold change of the up- and down-regulated lnc RNAs, whereas TBC1D17 and CCL3L3 had the highest foldchange of the up- and down-regulated m RNAs. Six（SNX1, CYFIP2, CD6, CMTM8, STAT4 and IGFBP7） of 10 m RNAs and 8（NR033913, NR038218, NR036512, NR049759, NR033951, NR045408, NR038377 and NR039976） of 14 lnc RNAs showed the same change trends on the microarray and q RT-PCR results with statistical significance. Based on the q RT-PCR verified m RNAs, 1358 potential lnc RNAs with 2697 positive correlations and 2287 negative correlations were predicted by the CNC network. CONCLUSION: The plasma lnc RNAs profiles provide preliminary data for the non-invasive diagnosis of CD and a resource for further specific lnc RNA-m RNA pathway exploration.